MENUMBUHKAN KREATIVITAS DALAM MENULIS TEKS DESKRISPSI DENGAN MENGGUNAKAN METODE PUZZLE AMPLOP DI MADRASAH TSANAWIYAH - Mia Jalilah; Dini Nur Fadillah; Cucu Kartini (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
The purpose of this paper is to describe the implementation of puzzle envelope method to grow creativity in writing description text, to describe the learning result of writing description text by using puzzle envelope method, and to describe the difficulties in learning to write description text using puzzle envelope method. This research uses quantitative experimental method with pre-experimental design. The technique of collecting data by using the technique of test and non-test. Techniques in the form of writing text description and techniques non-test form of observation. The result of research at the pretest stage obtained an average value of 62.03 whereas after getting the treatment by using puzzle envelope method (posttest) obtained the average value 82.03. Based on the results obtained show that puzzle envelope method can be used to cultivate the creativity of writing description text in Madrasah Tsanawiyah.